2019
DOI: 10.1002/cctc.201900556
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Homocoupling of Arylboronic Acids Catalyzed by Regenerable Pd(II)@MIL‐88B‐NH2(Cr)

Abstract: A fast and operationally simple method for the aerobic homocoupling of arylboronic acids is described. The process is catalyzed by Pd(II) complexes supported on the metal‐organic framework MIL‐88B‐NH2(Cr). The benefits of this approach include the use of a benign oxidant/solvent mixture at room temperature with catalytic amounts of base, easy recovery of the catalyst, and easy isolation of the products. Very high conversions and good yields were achieved for a variety of substrates, and the process was also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…13 C NMR (101 MHz, CDCl 3 ) δ=153.3, 137.5, 137.5, 104.5, 60.9, 56.2.ppm. Data was in accordance with that reported in the literature [23] …”
Section: Methodssupporting
confidence: 92%
“…13 C NMR (101 MHz, CDCl 3 ) δ=153.3, 137.5, 137.5, 104.5, 60.9, 56.2.ppm. Data was in accordance with that reported in the literature [23] …”
Section: Methodssupporting
confidence: 92%
“…It is essential to have a fast and reliable procedure that can be used to prepare a range of materials that will allow the identification of the one with the highest catalytic activity. Our group has extensive experience in the synthesis of diverse materials and its application in catalysis. …”
Section: Introductionmentioning
confidence: 99%
“…A common method for the preparation of symmetrical biaryls depends on palladium catalysis in the presence of related ligands, bases, and solvents [9]. Valiente et al reported the aerobic homocoupling of arylboronic acids catalyzed by Pd(II) complexes, but this method requires special Pd(II)@MOF species, which limits its large-scale use [10]. Demir et al found that copper(II) acetate could mediate the homocoupling of arylboronic acids [11].…”
Section: Introductionmentioning
confidence: 99%